2016
DOI: 10.5433/1679-0359.2016v37n2p1091
|View full text |Cite
|
Sign up to set email alerts
|

Dual purpose wheat production with different levels of nitrogen topdressing

Abstract: Currently, the practice of Crop-Livestock Integration is stimulated as a way of increasing the generation of foreign exchange for Brazil. Integrated systems improve land use efficiency as well as preserve, recover and increment or soil fertility. The aim of this research was to evaluate how different doses of nitrogen fertilization can affect production and quality of dual purpose wheat submitted to grazing. The experimental designed was randomized block with five treatments (0, 75, 150, 225 and 300 Kg N ha -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…Juskiw et al (1991) assessed rye and triticale as monocultures associated with barley and observed a CP content over 190 g /kg DM for both cereals sown in the same season. WHT and TRT treatments had CP values similar to reports by Henz et al (2016) and Khorasani et al (1997).…”
Section: Discussionsupporting
confidence: 80%
“…Juskiw et al (1991) assessed rye and triticale as monocultures associated with barley and observed a CP content over 190 g /kg DM for both cereals sown in the same season. WHT and TRT treatments had CP values similar to reports by Henz et al (2016) and Khorasani et al (1997).…”
Section: Discussionsupporting
confidence: 80%
“…Feed should contain a satisfactory concentration of proteins and nonfibrous carbohydrates (starch and soluble sugars), the latter being the most important source of energy produced in the rumen. This concentration stimulates the growth of bacteria and increases the production of microbial protein and volatile fatty acids necessary to induce the milk or meat response (Henz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Quatrin et al (2017) evaluated the same wheat cultivar with 130 kg N ha -1 as urea under grazing by lactating cows and verified a daily accumulation rate of 40.78 kg and a dry matter production of 4,143 kg. Henz et al (2016) evaluated BRS Tarumã managed with different doses of nitrogen as topdressing (0, 75, 150, 225 and 300 kg N ha -1 as urea) and grazed by lactating Holstein cows found that accumulation rate presented a quadratic upward trend with a maximum point close to treatment 150 and greater than 100 kg dry matter per day. The experiments mentioned, along with the results obtained in the present experiment demonstrate the ability of regrowth and production of wheat, but it is important to emphasize that the growth rates were changed exponentially with the different doses of nitrogen as topdressing.…”
Section: Discussionmentioning
confidence: 99%
“…However, some dual-purpose cultivars have been used only for grazing, due to the quantity and quality of the forage produced, which are due to the number of inputs applied and mainly the management. According to Henz et al (2016) the use of dual-purpose wheat for grazing allows for early cropping by minimizing and/or nullifying the effects of forage shortage in the fall.…”
Section: Introductionmentioning
confidence: 99%